Evaluating the role of serum uric acid in the risk stratification and therapeutic response of patients with pulmonary arterial hypertension associated with congenital heart disease (PAH-CHD) - Luo, Jun; Li, Yuanchang; Chen, Jingyuan; Qiu, Haihua; Chen, Wenjie; Luo, Xiaoqin; Chen, Yusi; Tan, Yingjie; Li, Jiang (Frontiers in Pharmacology, 2023)
Background: Pulmonary arterial hypertension (PAH) is a malignant pulmonary vascular disease that negatively impacts quality of life, exercise capacity, and mortality. This study sought to investigate the relationship between serum uric acid (UA) level and the disease severity and treatment response of patients with PAH and congenital heart disease (PAH-CHD). Methods: This study included 225 CHD patients and 40 healthy subjects. Serum UA was measured in all patients, and UA levels and haemodynamic parameters were re-evaluated in 20 patients who had received PAH-specific drug treatment for at least 7±1 months. Results: Serum UA levels were significantly higher in PAH-CHD patients than in CHD patients with a normal pulmonary artery pressure and normal subjects (347.7± 105.7μmol/L vs 278.3±84.6μmol/L; 347.7±105.7μmol/L vs 255.7±44.5μmol/L, P<0.05). UA levels in the intermediate and high risk groups were significantly higher than those in the low-risk group (365.6±107.8μmol/L vs 311.2±82.8μmol/L; 451.6±117.6μmol/L vs 311.2±82.8μmol/L, p<0.05). Serum UA levels positively correlated with mean pulmonary arterial pressure, WHO functional class, pulmonary vascular resistance, and NT-proBNP (r=0.343, 0.357, 0.406, 0.398; p<0.001), and negatively with mixed venous oxygen saturation (SvO2) and arterial oxygen saturation (SaO2) (r=−0.293, −0.329; p<0.001). UA significantly decreased from 352.7±97.5 to 294.4±56.8μmol/L (p=0.001) after PAH-specific drug treatment for at least 6 months, along with significant decreases in mean pulmonary arterial pressure and pulmonary vascular resistance and increases in cardiac index and mixed SvO2. Conclusion: Serum UA can be used as a practical and economic biomarker for risk stratification and the evaluation of PAH-specific drug treatment effects for patients with PAH-CHD.